Profil Leukosit Serta Imbangan Neutrofil dan Limfosit pada Kambing Peranakan Etawah yang Sedang Bunting - Widhyari, Sus Derthi; Widodo, Setyo; Wibawan, I Wayan Teguh; Esfandiari, Anita; Choliq, Chusnul (Jurnal Veteriner; Vol 21 No 4 (2020), 2020)
This research aimed to determine the profiles of total leukocytes and neutrophil -lymphocyte ratio (N/L) in pregnant etawah crossbreed goats. Six etawah crossbreed goats around 3-6 years old and body weight around 30-50 kg were used in this study. Blood samples were taken from jugulars vein in non pregnant (K), and at gestational age 12, 14, 16 and 18 weeks. Blood is inserted into a tube that contains EDTA (Ethylene Diamine Tetraacetic Acid) anticoagulant to obtain whole blood. Whole blood were analyzed to total leukocyte cells and leukocyte types. The results showed that total leukocytes profiles tend to increase during pregnancy. Lymphocytes stable until 16 weeks of pregnancy and tends to decrease at the end of pregnancy. The N/L ratio increase at the end of pregnancy, this condition indicates an increase in the number of neutrophils accompanied by decreased lymphocyte cells and can be found in etawah crossbreed at 18 weeks of gestation.